RELAS I SOSIAL KELAYAN TUNANETRA DI PANTI SOSIAL BINA N ETRA TUAH SAKATO PADANG (Deskriptif Kualitatif) - WINNI FERAH (Jurnal Penelitian Pendidikan Khusus, 2015)
ABSTRACT This research discussed  about the social relation.  This researc h was intended to describe the process of social relation in the preparation class covering sveral indicators such as the process, obstracles, and the efforts done. This research was conducted at PSBN Tuah Sakato Padang. This research applied descriptive qualitative approach   focusing on the process of social relation for the clients with visual impairment. The subject of the research was the head of the institution, the teachers  handling  skill classes,  the subject teachers,  the Guidance and  and  Counseling teachers, the psychology teachers, and the clients in the preparation class. The data were collected through observation, interview and documentation study. The results of the research showed that  the social relation in the preparation class existed  in  all  of subject,  while  the  implementation  was  more  significant  in  mobility orientation subject. The guidance was given only 3 hours in a single meeting a week. The evaluation was done once in three months or four times in a year. The learning materials were taught repeatedly so that the clients had deep  understanding on them. The clients living in the house were those who neither went to regular nor to special school previously, and  they  had  low intelligence.  In the future,  it was expected  to  the  intructors  and the institution fellows to provide more times to the clients to get intensely guidance in mobility orientation subject whose materials required the students to do a lot of practice.